2023
DOI: 10.3171/2023.2.jns221477
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient telemedicine in neurosurgery: 15,677 consecutive encounters in a comparative analysis of its effectiveness and impact on the surgical conversion rate

Abstract: OBJECTIVE The coronavirus disease 2019 (COVID-19) pandemic has necessitated the use of telehealth visits (THVs). The effects on neurosurgical practice have not been well characterized, especially concerning new-patient THVs. Therefore, the authors of this study reviewed their institution’s experience with outpatient clinic visits and THVs from before the COVID-19 pandemic to the present to focus on clinical metrics, rates of surgery, and the effects of implementing THVs in order to better understand their impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The limitations of telemedicine described included the impossibility to perform physical examinations (42%), the inability of patients to use technology (24%) and to work with elderly patients (20%). Hopkins et al [ 26 ] reviewed new outpatient in-person visits (IPVs) and telehealth visits (THVs) and found that THVs did not increase the duration of follow ups. Porche et al [ 27 ] evaluated patient satisfaction scores of telemedicine clinic visits in neurosurgery in comparison to in-person visits in neurosurgical clinics in Florida, USA.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of telemedicine described included the impossibility to perform physical examinations (42%), the inability of patients to use technology (24%) and to work with elderly patients (20%). Hopkins et al [ 26 ] reviewed new outpatient in-person visits (IPVs) and telehealth visits (THVs) and found that THVs did not increase the duration of follow ups. Porche et al [ 27 ] evaluated patient satisfaction scores of telemedicine clinic visits in neurosurgery in comparison to in-person visits in neurosurgical clinics in Florida, USA.…”
Section: Discussionmentioning
confidence: 99%